Smart Labourer – A Proposed System for locating Labourers - Ahmed, Mohammed; Iraqui, Shamshad; Ansari, Masood; Ansari, Abdul Qadir (International Journal of Computer Sciences and Engineering, 2019)
It is very challenging for a contractor to procure skilled/ semi-skilled manpower for the various construction activates. On other side labourers are going through lots of hardships. Labourers who work on daily or hourly wages in any construction work find it very difficult to get a job. Generally labourers gathering at a place like railway station or bus stop etc. every morning in search of jobs. If they have to spend their whole day without work then it will become difficult for their family to survive. There are many middlemen working between worker and contractor, they take commission from both parties workers and contractors. They offer jobs only to those workers who give them good commission and ignore others. Contractors also have to give commission to the middlemen and because of this labourers get lesser than the expected wages. This system will eliminate the middlemen agents and hence commission from the labourers. This System will also provide full wages to labourers by contractors which were previously cut by middlemen/agents. Instead of agents there will be placement agencies which will help the labourers offering jobs and these placement agencies will be paid by contractors depending upon the amount of work and number of labourers. This will gradually increase the jobs seeking for labourers and eliminate unemployment for labourers. Hence, our system will be helpful for contractors for finding labourers and also be helpful for needy labourers who work on wages.